On the difference between γ-ray-detected and non-γ-ray-detected pulsars. Issue 2 (31st October 2016) - Rookyard, S. C.; Weltevrede, P.; Johnston, S.; Kerr, M.
Abstract: We compare radio profile widths of young, energetic γ-ray-detected and non-γ-ray-detected pulsars. We find that the latter typically have wider radio profiles, with the boundary between the two samples exhibiting a dependence on the rate of rotational energy loss. We also find that within the sample of γ-ray-detected pulsars, radio profile width is correlated with both the separation of the main γ-ray peaks and the presence of narrow γ-ray components. These findings lead us to propose that these pulsars form a single population where the main factors determining γ-ray detectability are the rate of rotational energy loss and the proximity of the line of sight to the rotation axis. The expected magnetic inclination angle distribution will be different for radio pulsars with and without detectable γ rays, naturally leading to the observed differences. Our results also suggest that the geometry of existing radio and outer-magnetosphere γ-ray emission models is at least qualitatively realistic, implying that information about the viewing geometry can be extracted from profile properties of pulsars.